Penerapan Preference Selection Index (PSI) Dalam Sistem Pendukung Keputusan Pengangkatan Supervisor Housekeeping - Rikky Panggabean; Nelly Astuti Hasibuan (STMIK Budi Darma, 2020)
Hotels are services that are managed commercially in order to provide lodging facilities to the general public. Grand Antares Hotel is a 4 (four) star hotel or